Se mejora la escolaridad con becas de mayor monto? La evidencia de las localidades urbanas de México - M. Caridad Araujo; María Adelaida Martínez; Sebastian Martinez; Michelle Pérez; Mario A. Sánchez (Inter-American Development Bank (IDB), 2018)
– We study the effects of increasing cash grants on the education attainment of low-income middle and high school students in Mexico. Starting in 2009, the Oportunidades conditional cash transfer (CCT) program increased the average grant in middle and high school by 27 percent for females and 30 percent for males in 263 of 630 urban localities in the country. Using administrative data sources and a difference-in-difference identification strategy, we find that students in households with larger grants exhibit lower dropout rates in middle school, and increase high school graduation by up to 33.5 percent. Effect sizes do not vary substantially by gender or baseline academic ability as measured by a standardized test. The expected future income from additional schooling exceeds the cost of the grants by a ratio of more than two-toone. The patterns we observe are consistent with an elastic demand for schooling, suggesting that increasing the school grant component of conditional cash transfers may be an efficient way to boost educational attainment for low-income students.
Keywords: I25; H53; I38; 330; Cash transfers; school dropout; high school graduation; Mexico; Progresa; Oportunidades; Prospera